Доктрина отказа от права: опыт сравнительно-правового анализа - Sarkisyan, Arutyun (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims at an analysis of the functioning of the notion of waiver in the civil law doctrine. The author present that act of one person that results in the surrender of a legal right in the context of comparative approach.
The waiver in civil law doctrine: experience of comparative legal analysis
Keywords: waiver; civil law; legal comparative